2019
DOI: 10.1007/s40626-019-00154-w
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and biomass accumulation in young sugarcane plants grown under increasing ammonium supply in nutrient solution

Abstract: The aim of this study was to evaluate the sugarcane responses to varying ammonium:nitrate (NH 4 ? :NO 3-) ratio and to reveal how much NH 4 ?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Our previous study revealed that sugarcane plants can be supplied with 30% NH 4 + in nutrient solution without compromising their photosynthesis and growth ( Pissolato et al, 2019a ). Thus, the NO 3 − :NH 4 + ratios 100:0 and 70:30 were chosen to represent the treatments with more and less NO 3 − , while supplying the same amount of nitrogen and avoiding NH 4 + toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study revealed that sugarcane plants can be supplied with 30% NH 4 + in nutrient solution without compromising their photosynthesis and growth ( Pissolato et al, 2019a ). Thus, the NO 3 − :NH 4 + ratios 100:0 and 70:30 were chosen to represent the treatments with more and less NO 3 − , while supplying the same amount of nitrogen and avoiding NH 4 + toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Some crops have a preference for NH 4 + uptake ( Malagoli et al, 2000 ), but most studies have reported stress symptoms associated with NH 4 + toxicity ( Barreto et al, 2018 ; Boschiero et al, 2019 ). While Robinson et al (2011) reported the sugarcane preference for NH 4 + , Pissolato et al (2019a) found that increasing NH 4 + supply causes biomass reduction and photosynthesis impairment of sugarcane plants. Changing the N source, NO 3 − supply has been shown to increase the tolerance to abiotic stresses in maize ( Rios-Gonzales et al, 2002 ) and grass species ( Wang and Macko, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that sugarcane plants can be supplied with 30% NH 4 + in nutrient solution without compromising their photosynthesis and growth (Pissolato et al , 2019). Thus, the NO 3 − :NH 4 + ratios 100:0 and 70:30 were chosen to represent the treatments with more and less NO 3 − , while supplying the same amount of nitrogen and avoiding NH 4 + toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf CO 2 assimilation ( A n ), stomatal conductance ( g s ) and the effective quantum efficiency of photosystem II (□ PSII ) were measured under PPFD of 2000 μmol m −2 s −1 and air CO 2 concentration of 400 μmol mol −1 . The measurements were performed between 10:30 and 12:30 h, as carried out previously (Pissolato et al , 2019). The vapor pressure difference between leaf and air (VPDL) was 2.1±0.2 kPa and leaf temperature was 30±0.4°C during the evaluations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation